Env-derived gp55 gene of Friend spleen focus-forming virus specifically induces neoplastic proliferation of erythroid progenitor cells. - Aizawa, S (1990)
A group of retroviruses carrying truncated viral genes has recently been suggested as the cause of new patterns of diseases. One such virus is the replication defective component of the Friend murine leukemia virus (F-MuLV) complex, called Friend spleen focus forming virus (F-SFFV). This virus induces erythroblastosis, and a virion envelope-related glycoprotein, gp55, encoded by F-SFFV has been suggested as the pathogenic gene. The role of the gp55 gene is, however, yet unclear in the apparently multistep erythroleukemogenesis. By separately producing transgenic mice harboring the whole F-SFFV DNA, the gp55 gene alone under the control of the retroviral long terminal repeat (LTR) and the gp55 gene under the control of cytoplasmic beta actin transcriptional regulatory unit, we show here that the gp55 gene is capable of inducing neoplastic proliferation of erythroid progenitor cells specifically in the absence of helper virus and other F-SFFV sequences. Under the control of the viral LTR the gp55 expression was detected only in leukemic tissues, but under the control of cytoplasmic beta-actin regulatory sequences, the gp55 was also expressed in a variety of normal tissues including preleukemic normal spleens. The development of erythroleukemia was suppressed under the genetic background of C57B1/6 mouse (resistant to F-MuLV; Fv-2rr), and required additional events even under the background of DDD mouse (susceptible to F-MuLV; Fv-2ss). The p53 and Spi-1 genes were frequently aberrant in transplanted tumors and cell lines derived from them, but were not in primary leukemic spleens.